2008
DOI: 10.1002/jmr.904
|View full text |Cite
|
Sign up to set email alerts
|

Phage display screening in low dielectric media

Abstract: Here we report the first application of phage display screening in low dielectric media. Two series of phage clones with affinity for alpha-chymotrypsin (CT) were selected from a Ph.D.(TM)-C7C library, using either a buffer or acetonitrile in buffer (50%, v/v). The affinity of lysates, individual clones or selected cyclic peptides for the enzyme was studied by examining their influence on CT activity. Peptides displayed on phage selected in buffer provided significant protection from enzyme autolysis resulting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…The concept of using phage display to develop biomolecular structures with function outside of a biological context, or even structures with functions not encountered in biology, is fascinating [ 4 ]. Nonetheless, this has received little attention to date with only a limited number of reports where the screening target is a material of non-biological nature [ 5 , 6 , 7 , 8 ], or where the screening is performed in an environment not generally encountered in biology [ 9 ]. In efforts towards engineering biomolecular structures capable of interaction with the surfaces of materials of non-biological origin, we undertook a proof-of-concept study using a cyclic heptapeptide phage library based upon the phagemid pG8H6.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of using phage display to develop biomolecular structures with function outside of a biological context, or even structures with functions not encountered in biology, is fascinating [ 4 ]. Nonetheless, this has received little attention to date with only a limited number of reports where the screening target is a material of non-biological nature [ 5 , 6 , 7 , 8 ], or where the screening is performed in an environment not generally encountered in biology [ 9 ]. In efforts towards engineering biomolecular structures capable of interaction with the surfaces of materials of non-biological origin, we undertook a proof-of-concept study using a cyclic heptapeptide phage library based upon the phagemid pG8H6.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously examined this phage with respect to its tolerance of organic solvents [ 10 , 11 ], where it was demonstrated that the phage could withstand significant concentrations of water miscible organic solvents, e.g., up to 99% acetonitrile. This surprising tolerance has been used by us for identifying peptides with affinity for alpha-chymotrypsin in media of low dielectricity [ 9 ]. The robustness of this phage is even demonstrated in its use for identifying peptides selective for synthetic polymers [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Peptides can be chemically conjugated to the phage, or displayed as recombinant fusions to the coat proteins [2]. The immunogenicity of short peptide epitopes is enhanced when they are displayed on the phage capsid, chemical stability is increased [3], cloning and purification protocols required to produce the immunogen are easy, and costs are very low [4]. Phage-based products have been recently approved in food safety by the US Food and Drug Administration (FDA) [5].…”
Section: Introductionmentioning
confidence: 99%
“…In broad terms, phage vaccines have several advantages relatively to the conventional ones (Clark & March, 2004a;Olofsson et al, 2008). Phage vaccines can be economically manufactured, due to the possibility of rapidly obtaining high phage titers on relatively inexpensive media, with straightforward purification steps.…”
Section: Phage-derived Vaccinesmentioning
confidence: 99%